PENGARUH PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL (StudiEmpirisPada Perusahaan ManufakturSektorIndustriBarangKonsumsiMakanandanMinuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2008-2012) - Hani Sri Mulyani (MAKSI, 2014)
This study has purpose to get empirical evidence about effect of profitability and sales growth to capital structure in the industrial sector manufacturing company of food and beverage consumption of Royal Securities Indonesia in the period 2008-2011.The methods used in this research is descriptive research using verifikatif and quantitative data analysis. Data collection technique used is to use fieldwork and study in library. The Data obtained were analyzed by means of a classic assumption test, an analysis of the correlation coefficient, coefficient of determination analysis, regression analysis, and test the hypothesis (t-test and F-test). Analysis results during the last four years earned a total of 48 samples of the company. Based on the partially result shows that that profitability and sales growth a positive and significant effect to capital structure. Based on simultaneously result shows that profitability and sales growth influence significantly to capital structure in manufacturing companies industry sector food and beverage consumption goods listed on the Indonesia stock exchange period 2008-2011.